2022
DOI: 10.4103/jcd.jcd_224_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial efficacy on Enterococcus faecalis and smear layer removal in curved canals by different irrigation techniques: An in vitro study

Abstract: Background: Various irrigation techniques have been proposed to improve the effectiveness of root canal debridement. Aims: The aim of the study was to compare the antimicrobial effect on Enterococcus faecalis and smear layer removal efficacy in curved canals by different irrigation techniques. Materials and Methods: Eighty extracted permanent maxillary molars with curved mesiobuccal roots were inoculated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…concluded that Er,Cr:YSGG laser-assisted irrigation offered better biofilm elimination in the apical root portions compared to syringe and ultrasonic irrigant agitation techniques. [ 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…concluded that Er,Cr:YSGG laser-assisted irrigation offered better biofilm elimination in the apical root portions compared to syringe and ultrasonic irrigant agitation techniques. [ 19 20 ]…”
Section: Discussionmentioning
confidence: 99%